Benefit of Ginkgo biloba for Dementia - Citra Ananta Avis (HM Publisher, 2021)
Dementia is a chronic progressive brain illness syndrome defined by the loss of numerous cognitive processes, including memory, aphasia, apraxia, agnosia, and executive function. Consciousness is usually unaffected. Psychological and behaviour issues are sometimes present. Dementia is caused by a number of diseases and accidents that affect the brain, either directly or indirectly, such as Alzheimer's disease or stroke. Vascular dementia is a loss of thinking capacity caused by disorders that impede blood flow to certain parts of the brain, depriving brain cells of oxygen and nutrients. After Alzheimer's disease, vascular dementia is the second most frequent kind of dementia. This case study looks at a 76-year-old woman who has vascular dementia. The goal of pharmacological management with risperidone in low dose, as well as psychotherapy, in patients is to preserve and maximize function, reduce behaviour problems, relieve caregiver stress, and delay advancement to the next level. Ginkgo Biloba is one of the plants classified as phytopharmacology or medicines derived from of the plant is Ginkgo biloba Plant G. biloba (Gb) is included in the family Ginkgoaceae. In the G. biloba extract has antioxidant, antiviral, anti-inflammatory, and anti-carcinogenic properties. And also have it was stated that G. biloba extract had a good effect on the function of the CNS (central nervous system).